Development and Validation of the Digestive Function Assessment Instrument for Traditional Korean Medicine: Sasang Digestive Function Inventory. (25th September 2013) - Lee, Misuk; Bae, Na Young; Hwang, Minwoo; Chae, Han
Abstract : Objective . This study was conducted for development and validation of the Sasang Digestive Function Inventory (SDFI) with type-specific digestive function-related symptoms for identification of Sasang type and pathological pattern. Methods and Materials . We selected questionnaire items for pathophysiological symptoms using internal consistency analysis and examined construct validity using 193 healthy participants. Test-retest reliability with a four-week interval as well as convergent validity was examined using the Nepean Dyspepsia Index-Korean (NDIK), Functional Dyspepsia-Related Quality of Life (FDQOL), Dutch Eating Behavior Questionnaire (DEBQ), and Body Mass Index (BMI). Results . The 21-item SDFI showed satisfactory internal consistency (Cronbach's alpha = 0.743) and test-retest reliability (r = 0.886, P < 0.001 ). Three extracted subscales, SDFI-Digestion, SDFI-Appetite, and SDFI-Eating pattern, explained 56.02% of the total variance. The SDFI showed significant (P < 0.001 ) correlation with total symptom score of NDIK, FDRQOL-Eating status, DEBQ-External Eating scale, and BMI. The SDFI score of the Tae-Eum (50.62 ± 8.05 ) type was significantly (P < 0.001 ) larger than that of the So-Eum (43.11 ± 11.26 ) type. Conclusion . Current results demonstrated the reliability and validity of the SDFI and its subscales, which can be utilized as an objective instrument for diagnosis of Sasang types and assessment of the type-specific digestive function.